Influence of a tundra freeze-thaw cycle on sulfide oxidation and metal leaching in a low sulfur, granitic waste rock. (January 2017) - Langman, Jeff B.; Blowes, David W.; Amos, Richard T.; Atherton, Colleen; Wilson, David; Smith, Leslie; Sego, David C.; Sinclair, Sean A.
Abstract: Drill cuttings were collected at 1 m depths from an instrumented, low sulfur, experimental waste rock pile containing a 4C-pyrrhotite that had been exposed to the extreme freeze-thaw cycle of a tundra climate. Boreholes were drilled from the top to base in the center of the pile and near the core-batter transition. Waste rock samples were analyzed for carbon, sulfur, and metal concentrations; sulfur oxidation states; and variation in iron and nickel forms due to oxidative dissolution of pyrrhotite. Results from X-ray absorption spectroscopy and aqueous extraction experiments were used to relatively compare samples from various depths in the boreholes, which indicate sulfide weathering fronts that decrease in intensity from the top to core to base at the center of the pile and from the core-batter transition to the center of the pile. The tundra climate and waste pile configuration produce a permafrost base, a seasonally frozen core, and an atmospheric-like zone near the surface. The fluctuation of the freeze-thaw cycle caused the greatest sulfide weathering near the surface and lesser weathering in the core and base of the pile. Metal- and sulfur-rich leachate from the higher weathering zone likely is collecting on a variable and seasonal frozen surface beneath the surface layer that causes metals and S to precipitate and (or) sorb during a portion of the year. The accumulation of sulfur and metals with the flux of this frozen surface produces a nickel and possibly an iron and sulfur enrichment zone beneath the surface layer in the center of the pile. The weathering front from the top to core to base of the pile and from core-batter transition to the core corresponds to a previously formulated leachate model, but the enrichment zone below the surface zone is unique to this conceptual waste-rock weathering model for this tundra climate. Highlights: The freeze-thaw cycle of a tundra climate causes differential sulfide weathering within waste rock. Vertical and horizontal weathering fronts were identified from pyrrhotite alteration. Differential weathering produced a spatial distribution of metal forms. A seasonal frozen surface likely retained leachate causing a nickel and sulfur enrichment zone. The tundra climate induces a seasonal cycle of metal sulfide weathering and element mobilization.